Modulation of HMGB1 Release in APAP-Induced Liver Injury: A Possible Strategy of Chikusetsusaponin V Targeting NETs Formation - Liu, Jian; Jiang, Min; Jin, Quan; Wu, Yan-Ling; Cui, Zhen-Yu; Cui, Ben-Wen; Shang, Yue; Zhan, Zi-Ying; Lin, Yong-Ce; Jiao, Jing-Ya; Piao, Mei-Hua; Zhang, Zhi-Hong; et al. (Frontiers in Pharmacology, 2021)
Acetaminophen (APAP), one of the most common antipyretic analgesics, which is safe at therapeutic dose, cause acute liver injury and even death at overdose. However, the mechanism of APAP-induced inflammation in liver injury is still controversial. Therefore, effective drug intervention is urgently needed. The aim of this study was to explore the inflammatory exact mechanism of APAP, especially on neutrophils, and to study the intervention effect of Chikusetsusaponin V (CKV) derived from Panax japonicus. Establishment of hepatotoxicity model of APAP in vitro and in vivo. In vitro, HepG2 cells, AML12 cells, primary mouse hepatocytes and neutrophils were used to mimic APAP-affected hepatocytes and neutrophil. In vivo, C57BL/6 mice were administrated overdose of APAP with or without neutrophil depletion or abolishing neutrophil extracellular traps (NETs) formation. In this study, APAP stimulation increased the level of HMGB1, IL-1β and Caspase-1 in mouse liver, especially hepatocytes, which had a synergistic effect with LPS/ATP combination. NETs were formatted at early stage of APAP or HMGB1-stimulated neutrophils’ damage. Conditioned mediums from APAP-treated hepatocytes induced more significant NETs than direct APAP stimulation. Neutrophil depletion or abolishing NETs formation decreased HMGB1 level, eventually blocked hepatocytes necrosis. CKV pretreatment interfered Caspase-1 activation and HMGB1 release in APAP-damaged hepatocytes. CKV also prevented NETs formation. These results indicate that the production of HMGB1 may depend on the activation of Caspase-1 and play a key role in liver inflammation caused by APAP. The cross-dialogue between hepatocytes and neutrophils can be mediated by HMGB1. Therefore, CKV has a positive intervention effect on NETs-related inflammation in APAP-damaged liver, targeting Caspase-1-HMGB1.